SENGKETA DALAM KONTRAK PENDANAAN DIGITAL: ANALISIS HUKUM KEPERDATAAN DAN ALTERNATIF PENYELESAIANNYA - Miftachul Ulum, Kefi; Ariyanti, Sari; Suganda, Rangga; Rahmawati, Dewi; Khotimah, Husnul (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
Securities crowdfunding is a service that funds MSMEs and start-up companies using standard agreements. The agreement used contains clauses containing moral hazard from the service provider company in the form of forcing service users not to involve the provider in the event of a dispute, whereas if the legal relationship is explained, the provider acts as an intermediary for service users with a central role, so that without the provider, such digital funding will not occur. This information technology-based funding activity is covered by Financial Services Authority Regulation No. 57 of 2020 concerning Securities Offerings through Information Technology-Based Crowdfunding Services and Financial Services Authority Regulation Number 16 of 2021 Amendment to Financial Services Authority Regulation Number 57 of 2020 concerning Securities Offerings Through Services Information Technology-Based Crowdfunding. The use of the standard agreement refers to Article 64(1) of POJK 57 2020 with the principles of balance, justice, and fairness. The agreement clause also contains unclear dispute resolution related to sharia funding, and service users will also experience the potential risk of disputes between organizers, issuers, and investors, as well as risks related to investment. Normative legal research is used as a research method that is classified in library research using a statute approach as an approach to contractual analysis and dispute resolution hierarchies by breaking down various laws and technical regulations from the Financial Services Authority. Analysis with this approach was found in the study of Article 1338 of the Civil Code requiring contracts to be made in accordance with the law, but the agreement clauses used did not apply the principles of justice, norms, and morality. Apart from that, a hierarchy was found in digital-based and offline-based dispute resolution with clustering the level of each problem or dispute. This level of clustering is a codification of the breakdown results carried out by the compiler of interrelated regulations, which are classified as internal dispute resolution and external dispute resolution.